STRATEGIES TO STUDENTS’ ACTIVENESS IN TEACHING SPEAKING - Furqon Edi Wibowo; Nandhita Ayun Puspita (IKIP Siliwangi, 2024)
The aims of this research were devided into two parts, (1) to describe strategies to students’ activeness in teaching speaking and (2) to explain students activeness to the speaking teaching strategies.This research used descriptive qualitative. The findings showed that there were eight strategies to students’ activeness in teaching speaking, including Cooperative Learning Strategies, Active Learning Strategy, Providing Students with Feedback, Role Play, Plenty of Practice, Problem - Based Learning Strategy (SPBM), Questioning to Check for Understanding, and Storytelling. Meanwhile, there were fifteen students’ activeness in teaching speaking, including students pay attention to the book, students speak actively during learning, students express their opinions, students ask questions about material they have not yet understood, students interact in discussion activities, students pay attention when the teacher explains the material, students take notes on the material presented by the teacher, students do the assignments given by the teacher, students raising their hands before asking, students respond to the teacher by answering questions and conveying their ideas, students think critically in solving problem, students search for and utilize every learning resource, students are interested in the teacher's delivery of material, students are eager to learn, and students effort to create a conducive learning atmosphere.